PENATALAKSANAAN RADIASI EKSTERNA KASUS KANKER NASOFARING TEKNIK 2D MENGGUNAKAN PESAWAT COBALT 60 - R. Prahardi; Guntur Winarno; Asumsie Tarigan; Elena Marliani (JRI (Jurnal Radiografer Indonesia), 2019)
Introduction: Nasopharyngeal cancer occupies the third place as a type of malignancy in the order of the number of patients receiving radiation treatment at the radiotherapy center in Indonesia. Treatment of nasopharyngeal cancer can be done with Radiotherapy or with Chemotherapy. In RSMS for nasopharyngeal cancer cases using 2D technique using cobalt plane 60. Methods: Data collection is done by monitoring the patient at the first time to the radiotherapy installation to complete the treatment. Patients were irradiated with 2D techniques using a Cobalt 60 type GWXJ80 NPIC plane and a HMD-IB type simulator. Results: 45-year-old male patients with stage IVA were irradiated using 2D techniques, with doses for opposite lateral left right field 35x2 Gy irradiation time 47 s, supraclavicula field 25x2 Gy radiation time 73 s, etxoid field 33x2 Gy time irradiation 75 s and 8x2 Gy AP-PA field booster. Conclusion: Management of external radiation of nasopharyngeal cancer cases in RSMS using 2D technique with cobalt plane 60. Fields used there are 4 ie etmoid field, supraclavicula, opposing lateral kIri and right, and AP-PA field for booster. Keywords: radiotherapy, nasopharyngeal cancer, 2 dimension (2D), cobalt 60, radiation procedure.